Chronic PD-1 Checkpoint Blockade Does Not Affect Cognition or Promote Tau Clearance in a Tauopathy Mouse Model - Lin, Yan; Rajamohamedsait, Hameetha B.; Sandusky-Beltran, Leslie A.; Gamallo-Lana, Begona; Mar, Adam; Sigurdsson, Einar M. (Frontiers in Aging Neuroscience, 2020)
Programmed cell death protein 1 (PD-1) checkpoint blockade with an antibody has been shown to reduce amyloid-β plaques, associated pathologies and cognitive impairment in mouse models. More recently, this approach has shown effectiveness in a tauopathy mouse model to improve cognition and reduce tau lesions. Follow-up studies by other laboratories did not see similar benefits of this type of therapy in other amyloid-β plaque models. Here, we report a modest increase in locomotor activity but no effect on cognition or tau pathology, in a different more commonly used tauopathy model following a weekly treatment for 12 weeks with the same PD-1 antibody and isotype control as in the original Aβ- and tau-targeting studies. These findings indicate that further research is needed before clinical trials based on PD-1 checkpoint immune blockage are devised for tauopathies.